Waste Management Practices in Developing Countries - Godfrey, Linda (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book provides insights into waste management practices in developing countries, and the application of research and innovation in finding appropriate solutions to improved waste management. The chapters have been selected with a focus on organic waste beneficiation, a significant waste stream in developing countries; the role of government and associated policy interventions; citizen behaviour in support of greater waste recycling; and the safe management of hazardous waste, particularly healthcare risk waste.